Galectin-3 Enhances Vascular Endothelial Growth Factor-A Receptor 2 Activity in the Presence of Vascular Endothelial Growth Factor - Cano, Issahy; Hu, Zhengping; AbuSamra, Dina B.; Saint-Geniez, Magali; Ng, Yin Shan Eric; Argüeso, Pablo; D’Amore, Patricia A. (Frontiers in Cell and Developmental Biology, 2021)
Galectin-3 (Gal3) is a carbohydrate-binding protein reported to promote angiogenesis by influencing vascular endothelial growth factor-A receptor 2 (VEGFR2) signal transduction. Here we evaluated whether the ability of Gal3 to function as an angiogenic factor involved VEGF. To address this possibility we used human retinal microvascular endothelial cells (HRECs) to determine whether exogenous Gal3 requires VEGF to activate VEGFR2 signaling and if Gal3 is required for VEGF to activate VEGFR2. VEGFR2 phosphorylation and HREC migration assays, following either VEGF neutralization with ranibizumab or Gal3 silencing, revealed that VEGF endogenously produced by the HRECs was essential for the effect of exogenous Gal3 on VEGFR2 activation and cell migration, and that VEGF-induced VEGFR2 activation was not dependent on Gal3 in HRECs. Gal3 depletion led to reduced, but still significant VEGF-induced cell function, suggesting that Gal3 enhances VEGF activity. Since Gal3 has been suggested to be a potential therapeutic target for VEGFR2-mediated angiogenesis, it is crucial to define the possible Gal3-mediated VEGFR2 signal transduction mechanism to aid the development of efficacious therapeutic strategies.